Penerapan Model Project Based Learning untuk Meningkatkan Motivasi Belajar Materi Durasi Waktu Siswa Kelas II B MINU Kedungrejo Waru, Sidoarjo - Putri Yasmin Fazia Risfi; Aulia Mufidatus Safiani; Nur Aisyatir Rodliyah; Ananda Chumairoh; Muchammad Bachrul Alam; Asnal Mala; Kadir Jailani (CV. ITTC INDONESIA, 2026)
Learning motivation is one of the important factors in the success of mathematics learning in elementary schools, especially in the material of time duration that requires a concrete and meaningful understanding of concepts. This study aims to determine the effectiveness of the implementation of Project Based Learning (PJBL) in improving the learning motivation of class 2B students at MINU Kedungrejo Waru, Sidoarjo. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles through the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 21 students. Data collection techniques were carried out through observation, interviews, tests, and documentation. The results of the study showed an increase in student learning motivation after the implementation of the PJBL model. In the first cycle, learning motivation was in the medium category with a percentage of 66.8%, then increased in the second cycle to 70.1% with a high category. This shows that Project Based Learning is effective in improving student learning motivation in mathematics learning class 2B at MINU Kedungrejo Waru, Sidoarjo.